Problems in the implementation of physiotherapy for BPJS patients in referral facilities: A review of regulation No. 28/2014 - Eko Purwoko; Erli Salia; Hambali Yusuf; Abdul Latif Mahfuz (Trigin Publisher, 2023)
This paper explains that health is a basic right and investment for the welfare of society. This study examines the law and problems encountered in the implementation of physiotherapy services for BPJS patients in advanced referral facilities, in accordance with Minister of Health Regulation No. 28/2014. The results show that the regulation only covers medical rehabilitation by specialist doctors, so not all physiotherapy services can be implemented properly. Other obstacles include administrative bureaucracy and difficulties for the community to access physiotherapy services directly. This study supports the improvement of health services and the reduction of administrative barriers in the BPJS system.